2021
DOI: 10.3390/ma14113073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graphene Oxide on Zero Shear Viscosity, Fatigue Life and Low-Temperature Properties of Asphalt Binder

Abstract: This study has investigated the impact of graphene oxide (GO) in enhancing the performance properties of an asphalt binder. The control asphalt binder (60/70 PEN) was blended with GO in contents of 0%, 0.5%, 1%, 1.5%, 2%, and 2.5%. The permanent deformation behavior of the modified asphalt binders was evaluated based on the zero shear viscosity (ZSV) parameter through a steady shear test approach. Superpave fatigue test and the linear amplitude sweep (LAS) method were used to evaluate the fatigue behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…GO is stably dispersed in asphalt, and by forming intercalation junctions, it can improve the high-temperature properties and heat aging resistance of asphalt but cannot improve the ability of asphalt to resist cracking [13]. GO has a significant contribution to the ability to resist rutting deformation, and GO can be perfectly distributed in the matrix asphalt, and the compatibility with asphalt is relatively good [14]. Graphene oxide was mixed with bromobutane to synthesize butylated graphene oxide composite material, and then compounded with styrene-butadiene-styrene (SBS) to prepare C 4 H 9 -GO/SBS-modified asphalt, which was mixed with 5% SBS-modified asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…GO is stably dispersed in asphalt, and by forming intercalation junctions, it can improve the high-temperature properties and heat aging resistance of asphalt but cannot improve the ability of asphalt to resist cracking [13]. GO has a significant contribution to the ability to resist rutting deformation, and GO can be perfectly distributed in the matrix asphalt, and the compatibility with asphalt is relatively good [14]. Graphene oxide was mixed with bromobutane to synthesize butylated graphene oxide composite material, and then compounded with styrene-butadiene-styrene (SBS) to prepare C 4 H 9 -GO/SBS-modified asphalt, which was mixed with 5% SBS-modified asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the viscosity of the asphalt, lowering the mix temperature to reduce heat consumption and promote sustainability [4][5][6]. GO-modified asphalt can resist the phase separation when preserved at high temperature [7]. GO can change the microstructure of asphalt and improve the adhesion between asphalt and aggregates [8].…”
Section: Introductionmentioning
confidence: 99%
“…The shear-thinning behavior has previously been reported for flow-aligning nematic LCs and GO suspensions [38,47,48]. Choi et al [38] and Adnan et al [49] investigated the viscosity of GO suspensions for shear rates up to 10 s −1 and showed that it increased for different concentrations of GO from the isotropic to discotic phase. Giudice and Shen [48] explored GO aqueous suspensions viscosity further, considering the higher shear rate of 10 2 s −1 , and showed that the shear-thinning behavior becomes more noticeable at higher concentrations.…”
Section: Concentrationmentioning
confidence: 75%